Prefactibilidad para la creación de una empresa dedicada a la elaboración de artesanías con material de reciclaje en el cantón Bolívar - Vélez Bravo, Nora Isabel (2014)
The present proyect was done with the purpose of evaluating the feasibility to create an Enterprise dedicated to the elaboration of handicrafts with recycling material; the research about the use of recycled material in Bolívar canton showed that the generated waste is taken to the dumping site in the highway to Tosagua. Besides, only 0.36% of the population recycles. Because of This it is important to continue with plans of integrated management to provide a better use for the waste that is reusable; the selection of handicrafts was done by relying in the opinion of the surveyed subjects, taking as reference the products that will have more demand in the market with a higher percentage are ring holders and earrings. The market analysis was carried out using the data sheet for the collection of information applied to the population economically active where they got concrete responses and useful to know the level of demand, the offer, and prices estimated according to economic level, which in his case is a minimum of 0.75% and máximum of $10; the economic evaluation was done through the investment with own resources with a total of $1,775.24 and external financing by means of a credit for a total of 2000 the evaluation indicators to know the feasibility used was VAN which got a value of 2,605.06 and a TIR of 30% concluding that with the research done has been demostrated that the proyect is feasible from This point of view , environmental and social.